Peran dan Sikap Nabi Ya’qub dalam Mengembangkan Karakter Anak Perspektif Al-Qur’an (TAFSE: Journal of Qur'anic Studies, 2022)
The role and attitude of an ideal father is as the Qur'an describes through the dialogue between the Prophet Ya'qub and his children. A father must be able to develop the character of his children with an educational role and attitude. The reality of today's society is contrary to the concept of the Qur'an, the father who is expected to become an educator is actually a figure who damages the image of the child through several cases of incest relationships. Therefore, this article discusses the role and attitude of Prophet Ya'qub in developing the character of his children, its impact and the actualization of the role and attitude of Prophet Ya'qub in developing the character of children in the present. This article is literature research using the maudhu'i method. The data were analyzed descriptively and analytically. This article shows that: first, in developing the character of the child, the Prophet Ya'qub was able to act as an open, loving, caring, listening and protecting communicator for his children and as avoidance of conflicts in the family. Secondly, the impact of the role and attitude of the Prophet Ya'qub towards his children was the formation of a positive character, his children dared to admit his mistakes in the past. Third, The actualization of Ya'qub's role and attitude can be done by reflecting on Ya'qub. A father is able to establish close and familiar communication with children and is able to establish a patient and forgiving attitude towards his children. Peran dan sikap seorang ayah ideal adalah sebagaimana yang digambarkan al-Qur`an melalui dialog antara Nabi Ya’qub dengan anak-anaknya. Seorang ayah harus mampu mengembangkan karakter anak-anaknya dengan peran dan sikap yang mendidik. Realita masyarakat zaman sekarang bertolak belakang dengan konsep al-Qur`an, ayah yang diharap menjadi pendidik justru menjadi sosok yang merusak citra anak melalui beberapa kasus hubungan incest. Oleh karena itu, Artikel ini membahas peran dan sikap Nabi Ya’qub dalam mengembangkan karakter anak-anaknya, dampaknya dan aktualisasi peran dan sikap Nabi Ya’qub dalam mengembangkan karakter anak-anak pada masa sekarang. Artikel ini merupakan  penelitian kepustakaan dengan menggunakan metode maudhu’i. Data dianalisis secara deskriptif analitis. Artikel ini menunjukkan bahwa dalam mengembangkan karakter anak, Nabi Ya’qub mampu berperan sebagai penjalin komunikasi yang terbuka, pengasih, penyayang, pendengar dan pelindung bagi anak-anaknya serta sebagai penghindar dari terjadi konflik di dalam keluarga. Dampak peran dan sikap Nabi Ya’qub terhadap anak-anaknya terbentuknya karakter positif, anak-anaknya berani mengakui kesalahan-kesalahannya di masa lalu. Aktualisasi peran dan sikap Ya’qub dapat dilakukan dengan bercermin pada Ya’qub, ia mampu menjalin komunikasi yang dekat dan akrab dengan anak-anak dan mampu membangun sikap sabar dan pemaaf terhadap anak-anaknya.
Keywords: Peran; Nabi Ya’qub; Karakter; Anak